Effectiveness of Cognitive Remediation in Early Versus Chronic Schizophrenia: A Preliminary Report - Deste, Giacomo; Barlati, Stefano; Galluzzo, Alessandro; Corsini, Paola; Valsecchi, Paolo; Turrina, Cesare; Vita, Antonio (Frontiers in Psychiatry, 2019)
Background: Many evidences have demonstrated the effectiveness of cognitive remediation on cognition and functioning in patients with schizophrenia. Some researchers speculate that cognitive deficits are more amenable to remediation during earlier phases of illness than in chronicity. Therefore, cognitive rehabilitation should be used as an early intervention, seeking to produce durable functional changes in the early course of schizophrenia. Although there is strong evidence that cognitive remediation is effective in adult schizophrenia, there is little evidence about its efficacy and long-term generalized effectiveness in the early course of the disease. In this paper we intended to investigate the possibility that cognitive remediation may produce more beneficial effects when applied in the early phase of the illness compared to chronic patients. Materials and Methods: Data were gathered from a database used for a previous study performed by our group, in which 56 patients with schizophrenia received a cognitive remediation intervention. In a post-hoc analysis, patients with a duration of illness shorter than 5 years were defined as “early course” patients, while patients with a duration of illness longer than 5 years were defined as “chronic”. Clinical, neuropsychological and functional outcome variables were assessed at baseline and after treatment. Result: Of the 56 patients included in the study, 11 were “early course” and 45 were “chronic”. Both the early course group and the chronic group showed significant improvements in all the clinical, neurocognitive and functional parameters analyzed. A significantly greater improvement in early course patients compared with chronic patients emerged in clinical and functional measures. No differential change was observed between early course patients and chronic patients in the cognitive composite score. Conclusion: Our study confirms the effectiveness of cognitive remediation in improving clinical, cognitive and functional parameters in patients with schizophrenia, both in patients in the early course, as well as in chronic patients. However, patients in the early course showed a differential, greater change in clinical and functional parameters compared to chronic patients. Although some limitations, this study confirms the effectiveness of cognitive remediation interventions, in particular if applied in the early course of the illness